Public Relations and Communication Management. Case of Peruvian Sea Institute (IMARPE) - Bobadilla Terán, Patricia (2016)
These days, Public Relations are getting more important prominence in public organizations; they are destined to be the agent of different communication process, either to improve organization image or to get better relations between the organization and its publics. The objective of this research is establishing a relation that exists between the Public Relations and the Communication Management in Instituto del Mar del Peru (IMARPE); Public Relations being conceived as discipline in charge of look out the organizational image and identify, and Communication Management as the administration of different flows and communication channels which could have the organization. The investigation method is descriptive, correlative, explanatory; quantitative non experimental type. The evaluated sample was of 196 coworkers of 520 coworker’s population, speaking of national coverage of IMARPE. The results of this work demonstrated the significant relation that exists among Public Relations and Communication Management, and how the correct application of communication techniques and tools can advantage the organizational communication in the institution.